Spray Freeze Dried Lyospheres® for Nasal Administration of Insulin - Tuğrul Mert Serim; Jan Kožák; Annika Rautenberg; Ayşe Nurten Özdemir; Yann Pellequer; Alf Lamprecht (MDPI AG, 2021)
Pharmacologically active macromolecules, such as peptides, are still a major challenge in terms of designing a delivery system for their transport across absorption barriers and at the same time provide sufficiently high long-term stability. Spray freeze dried (SFD) lyospheres® are proposed here as an alternative for the preparation of fast dissolving porous particles for nasal administration of insulin. Insulin solutions containing mannitol and polyvinylpyrrolidone complemented with permeation enhancing excipients (sodium taurocholate or cyclodextrins) were sprayed into a cooled spray tower, followed by vacuum freeze drying. Final porous particles were highly spherical and mean diameters ranged from 190 to 250 µm, depending on the excipient composition. Based on the low density, lyospheres resulted in a nasal deposition rates of 90% or higher. When tested in vivo for their glycemic potential in rats, an insulin-taurocholate combination revealed a nasal bioavailability of insulin of 7.0 ± 2.8%. A complementary study with fluorescently labeled-dextrans of various molecular weights confirmed these observations, leading to nasal absorption ranging from 0.7 ± 0.3% (70 kDa) to 10.0 ± 3.1% (4 kDa). The low density facilitated nasal administration in general, while the high porosity ensured immediate dissolution of the particles. Additionally, due to their stability, lyospheres provide an extremely promising platform for nasal peptide delivery.